Survival and shelf life of Lactobacillus lactis 1464 in shrimp feed pellet after fluidized bed drying - Wirunpan, Maneerat; Savedboworn, Wanticha; Wanchaitanawong, Penkhae (Agriculture and Natural Resources, 2016)
In the present study, Lactobacillus lactis 1464 was attempted to be incorporated in shrimp feed pellets. The fresh culture (25% volume per weight) with and without pH adjustment was mixed into feed ingredients prior to the pelleting process at ambient temperature. The wet pellets were dried using a fluidized bed dryer at 50 oC, 60 oC, 70 oC and 80 oC to achieve a moisture content below 11%. The results indicated that the strain viability depended on the drying temperature with a viable cell number of approximately 106108 CFU/g and the pH of the culture was found to affect the strain viability during drying. At all drying temperatures, the strain survival after drying ranged from 75.94% to 92.28% at pH 3.8 and from 89.54% to 96.87% at pH 7.0. Moreover, the addition of protectants was found to enhance the strain survival during drying. In particular, milk powder and monosodium glutamate (MSG) exhibited significant (p < 0.05) protective effect on the viability at a high temperature of 80 oC. During storage at 30 oC, a high survival rate was found for the strain with MSG and acacia gum. Furthermore, the prediction model for long-term storage stability of the strainwas found to validate only at a low temperature of 4 oC, in comparison to a high temperature of 30 oC.